2009
DOI: 10.3139/146.110224
|View full text |Cite
|
Sign up to set email alerts
|

Technical parameters affecting grain refinement by high pressure torsion

Abstract: High pressure torsion is a well known and widespread processing technique for severe plastic deformation. The aim of high pressure torsion and other comparable techniques is to obtain ultrafine-grained or even nanocrystalline materials with enhanced mechanical and physical properties compared with their coarse-grained counterparts. Generally this refinement process is strongly influenced by processing parameters such as temperature or accumulated strain, but can also simply be affected by the entire experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
109
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 173 publications
(125 citation statements)
references
References 23 publications
10
109
1
Order By: Relevance
“…This is supported by the differences in microstructural observations along this direction. A sufficient high number of turns may reduce heterogeneity, by filling the alloy in-between the anvils and achieving a significant sticking condition which then increases the deformation and microstructural homogeneity [5,12,15,40,41]. The distribution of microhardness along the vertical and horizontal cross-sections showed considerable consistency for the current alloy processed at each specific processing temperature.…”
Section: Development Of Microhardnessmentioning
confidence: 94%
See 2 more Smart Citations
“…This is supported by the differences in microstructural observations along this direction. A sufficient high number of turns may reduce heterogeneity, by filling the alloy in-between the anvils and achieving a significant sticking condition which then increases the deformation and microstructural homogeneity [5,12,15,40,41]. The distribution of microhardness along the vertical and horizontal cross-sections showed considerable consistency for the current alloy processed at each specific processing temperature.…”
Section: Development Of Microhardnessmentioning
confidence: 94%
“…The feasibility of HPT processing at 296 K for the AZ91 magnesium alloy can be attributed to the presence of hydrostatic pressure, which prevents propagation of fracture during processing [6][7][8]. Furthermore, the geometry of the processing zone constrains the alloy within a specific volume as illustrated earlier and thus activation of twinning [8,15,16]. The XRD observations indicate the orientation of the processed microstructure towards twinning and basal deformation modes under HPT conditions that facilitate processing at room temperature [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Processing by HPT is usually undertaken on disk-shaped specimens, 31 although the processing has been extended also to cylindrical [32][33][34] and sheet 35 samples. The conventional HPT disks are generally cut from a single metal or alloy, but recently it was shown that semicircular disks of Al and Cu may be successfully bonded through a solid-state reaction at ambient temperature by using HPT processing through up to 100 turns.…”
Section: Fabricating High-strength Metal-matrix Nanocomposites By Higmentioning
confidence: 99%
“…Two important factors that are essential for the torsional straining of disc samples during HPT processing are hydrostatic pressure and micro-roughness of the anvil cavity surface [8]. For torsional straining a minimum pressure is needed in order to obtain sufficient frictional force so that no relative sliding between the anvil and the specimen surface occurs.…”
Section: Introductionmentioning
confidence: 99%